Análisis descriptivo de los resultados de las pruebas Sabre Pro en la UPTC del periodo 2012-2015 - Ayala Sánchez, Yolima (Universidad Pedagógica y Tecnológica de Colombia, 2017)
One way to measure the quality of higher education is through the assessment of competences in its students, which is done through the instrument known as the Saber Pro test. This document relates a descriptive analysis of the results obtained in the Saber Pro tests, in relation to generic competences of students of the Universidad Pedagógica y Tecnológica de Colombia (UPTC) who presented the test in the period 2012 to 2015. A quantitative review is carried out with the average scores obtained for each of the programs and qualitative type with the categories provided by ICFES, in the performance levels for the English module and by quintiles for the other evaluation modules.